2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943871
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-efficient robust biometric identification from 0.58 second template and 12 features of limb (Lead I) ECG signal using logistic regression classifier

Abstract: The electrocardiogram (ECG), widely known as a cardiac diagnostic signal, has recently been proposed for biometric identification of individuals; however reliability and reproducibility are of research interest. In this paper, we propose a template matching technique with 12 features using logistic regression classifier that achieved high reliability and identification accuracy. Non-invasive ECG signals were captured using our custom-built ambulatory EEG/ECG embedded device (NeuroMonitor). ECG data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Moreover it depicts significant variation of results among different subjects, since no two people are identical in terms of brain activities. From the study shown here, and other related study reported elsewhere [19,[21][22][23][24], the functionality and usability of the small and wearable NeuroMonitor device has been demonstrated for neuro-physiological data acquisition and applications.…”
Section: Evaluation Through Deploymentsupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover it depicts significant variation of results among different subjects, since no two people are identical in terms of brain activities. From the study shown here, and other related study reported elsewhere [19,[21][22][23][24], the functionality and usability of the small and wearable NeuroMonitor device has been demonstrated for neuro-physiological data acquisition and applications.…”
Section: Evaluation Through Deploymentsupporting
confidence: 54%
“…The device was configured for two channel referential montage with online mode. PSD of Alpha (8-13 Hz), Beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and Theta (4-8 Hz) rhythms from FP2 location are plotted in Fig. 8 for four subjects (denoted with different colours).…”
Section: Evaluation Through Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…This recording method is referred to as lead-1 ECG configuration recording. It is the most practical ECG recording method for biometric applications [28]. MD100E handheld ECG machine as shown in Figure 3 is used to record the ECG signal in our study.…”
Section: Simulation Setupmentioning
confidence: 99%
“…To evaluate the performance of the DLDV features extracted by our method, we employ four traditional classifiers (Gaussian Kernel Support Vector Machines (G-SVM) [43], Logistic Regression (LR) [44], Random Forests (RF) [45], and K-Nearest Neighbors (KNN) [46], and the parameter settings of each classifier are shown in Table 3) and six time-frequency dependent SQIs [10,47,48], such as sSQI and kSQI, pSQI, LpSQI, MpSQI, HpSQI. Table 4 shows the binary classification results of ECG signal quality using Fig.…”
Section: Performance Evaluation Of Dldv Featuresmentioning
confidence: 99%